Lecture Comprehension in English-Medium Higher Education - Hellekjær, Glenn Ole (HERMES - Journal of Language and Communication in Business, 2010)
In European higher education the growing number of English-Medium (EM) courses, i.e. non-language subjects taught through English, has led to discussion about, and research on, whether the use of a foreign language for instruction has a negative impact on teaching and learning. The present quantitative study investigates this issue by comparing student lecture comprehension in English and the ﬁrst language (L1) at three Norwegian and two German institutions of higher education, with a sample comprising 364 Norwegian and 47 German student respondents. It compares self-assessment scores for lecture comprehension in English and the L1. Analysis shows that while the difference between English and L1 scores was not substantial, a considerable number of students still had difﬁculties understanding the English-Medium lectures. Among the main problems, which in fact were similar in English and the L1, were difﬁculties distinguishing the meaning of words, unfamiliar vocabulary, and difﬁculties taking notes while listening to lectures. The study argues the need to improve the quality of lecturing in English and L1 as well as the lecturers’ and students’ English proﬁciency.